(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
This article presents chosen aspects of education and teaching with usage of modern didactic means, so- called e- learning, like : television, broadcasts,network, teleconferences and applications of computer programs, multimedia-virtual presentations. The role of such modern didactic means and their influence on the intensification and modernity of teaching had undergone analisis. We cannot use these without clearly directed aims and contents, though. Not to mention coherent methods of education and, finally, supervision or control